School-Based Approaches in Addressing Suicidal Behavior among High School Students: A Perspective from Filipino Guidance Counselors - Mary Anne Cupo; Teresita Rungduin; Carolina Dordas (Journal of Education and Counseling (JECO), 2025)
For some, schools are more than just places to learn. They serve as sanctuaries for students. Recent reports indicate a troubling rise in suicide rates among Filipino students, requiring urgent attention. Despite implemented solutions, new challenges continue to emerge, calling for ongoing work. Hence, this study explored the practical interventions and counseling techniques of four registered guidance counselors and one guidance associate in handling cases of suicidal behavior among high school students, the factors influencing the selection and application of these interventions and techniques, and the process of assessing the effectiveness of interventions in addressing suicidal behavior using data from semi-structured interviews analyzed through Giorgi and colleagues’ descriptive phenomenological analysis (2017). Key interventions include integrating various counseling techniques, tailoring individualized support strategies to students’ unique needs, and implementing structured referral systems that encourage collaboration with parents and other relevant stakeholders. The results provide important insights into the strategies utilized by school personnel to address suicidal behavior among students. These outcomes underscore the need for ongoing refinement in addressing mental health concerns, highlighting the importance of a collaborative and adaptive approach to ensure student well-being.